Interleukins in Thyroid Cancer: From Basic Researches to Applications in Clinical Practice - Xi, Chuang; Zhang, Guo-Qiang; Sun, Zhen-Kui; Song, Hong-Jun; Shen, Chen-Tian; Chen, Xiao-Yue; Sun, Jian-Wen; Qiu, Zhong-Ling; Luo, Quan-Yong (Frontiers in Immunology, 2020)
Inflammation is a crucial component of tumor progression, and some inflammatory molecules detected in the tumor microenvironment exert pro- or anti-tumorigenic effects. Interleukins are small protein signaling molecules that belong to the superfamily of cytokines and are mainly produced by CD3+ and CD4+ T lymphocytes. It usually plays significant roles in many solid cancers, because they are involved in systemic inflammation and immune system regulation. To date, numerous studies have confirmed interleukins are significantly associated with thyroid cancer. Interleukins could have clinical utilities in discriminating benign and malignant thyroid diseases, predicting the risk of tumorigenesis, evaluating the prognosis and monitoring the recurrence of thyroid cancer patients. Besides, the effective of treatment of thyroid cancer targeting on interleukins has been confirmed by some cell and animal researches, which indicates interleukins could be potential research direction of treatment of thyroid cancer. The present review will concentrate on the roles of interleukins in the diagnosis and treatment of thyroid cancer and introduce the potential mechanism of interleukins in the development of thyroid cancer, which will help update understanding of the progress of interleukin research in thyroid cancer.